Edukasi Gizi Spesifik Sebagai Gerakan 1000 Hari Pertama Kehidupan (HPK) Dalam Upaya Pencegahan Stunting Balita Pada Siswi di SMK Farmasi Al Furqan Banjarmasin - Khairul Anam; Norfai Norfai; Meilya Farika Indah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The purpose of this service is to transform and increase student knowledge about specific nutrition in the First 1000 Days of Life. The counseling method is carried out with two methods, namely the lecture method and the discussion method that uses media of power points. Before starting the counseling, a pretest activity is conducted on